Hepatoprotective effect of Acantholimon bracteatum (Girard) Boiss. on formaldehyde-induced liver injury in adult male mice - E. Nasiri; S. Naserirad; A. Pasdaran Lashgari; R. Gazor; F. Mohammadghasemi; Z. Atrkar Roushan (Iranian Society of Pharmacognosy, 2016)
Background and objectives: Acantholimon bracteatum (Girard) Boiss (Plumbaginaceae) is used in variety of diseases including hepatic ailments in the west regions of Iran. In the present study, the hepatoprotective effect of the methanol extract (ME) of A. bracteatum on formaldehyde (FA) induced liver injury has been investigated in adult male mice. Methods: Fifty six adult male mice were divided into 8 groups. The control group received normal saline. Group II (E2) was treated with formaldehyde 10 mg/kg. Group III to VIII (E3-E8) were treated with both FA (10 mg/kg) and the metanol extract at doses of 5, 10, 15, 20, 50 and 100 mg/kg, respectively. All animals were treated for 2 weeks (once every other day). At the end of the morphology, histopathology of liver and serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP) were evaluated. Results: Formaldehyde induced liver damage both in histology and function. The levels of ALT, AST and ALP enzymes had signiﬁcantly increased in FA treated group. Administration of ME in all experimental groups significantly reduced serum levels of ALP (p= 0.02); however, AST was reduced significantly just in groups III (E3) and IV(E5) (p